Peningkatan Sadar Lingkungan Generasi Muda Ikatan Pelajar Muhammadiyah (IPM) Melalui Kegiatan Penghijauan Memanfaatkan Tanaman Produktif - Suharno Suharno; Rosye Hefmi Rechnelty Tanjung; Irma Rahayu; Alpredo Dias Agape L. Toruan (Universitas Muhammadiyah Semarang, 2025)
The environment faces many important issues that must be resolved immediately because they can negatively impact various forms of life, including humans. One common problem is the lack of maintenance, which leads to the decline of forest areas and marginal land. Since plants play a vital role in human life, conservation and reforestation efforts are necessary to restore the land and maintain the balance of life. This activity aims to raise environmental awareness among the younger generation through productive plant-based greening activities. Methods include focus group discussions (FGDs), planting on marginal land, and evaluation. This activity was carried out in Jayapura City in collaboration with the Papua Environmental Council (MLH) and the Papua Province chapter of the Muhammadiyah Student Association (IPM). The practical planting activity with productive plants took place on barren land in the Koya Barat area of the Muhammadiyah apartment complex in Jayapura City. Based on the evaluation results, it was found that, before the activity, participants had a good understanding of basic environmental knowledge, reaching 96%. This increased to 100% after the activity. Understanding of protecting the environment and biological resources increased by 26.16%, rising from 76.44% to 96.44%. Understanding of land rehabilitation and reforestation increased by an average of 79.17%, rising from 57.33% to 97.33%. These increases are significant because they demonstrate substantial improvement. Participants responded positively to the material, with 84.8% strongly agreeing and 15.25% agreeing